Risk Assessment of Noise Pollution in a Cement Plant: Perspectives and Recommendations (Global Journal of Medical Research, 2023)
Introduction Noise is an acoustic phenomenon producing an auditory sensation considered unpleasant or annoying Exposure to high sound levels over 85 dB A can affect the auditory system and other extra-auditory systems Our study had the general objective of evaluating the impact of noise related to noise exposure in the Lafarge Holcim Guinea factory Material and methods This was a prospective descriptive study lasting 6 months from March 01 2022 to September 01 2022 It focused on the 150 workers at the Lafarge Holcim Guinea plant and their work areas
Keywords: risk-noise – evaluation – factory – FSTS